Phytochemical and Antioxidant Profiling of Allium Sativum Germinated under Biotic and Abiotic Stress - Samiah Shahid, Wajeehah Shahid, Amna Ihsan, Fozia Anjum, Muhammad Shahid (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: The purpose of the study is to evaluate the potential of Allium sativum under biotic and abiotic stress in the quest to obtain more efficient phytoconstituents with improved antioxidant properties. Method: We investigated the effect of stress induction through biotic (Fusarium solani) and abiotic (NaCl salt of two different concentrations i.e. 50 mM and 100 mM) means in Allium sativum (garlic) to uncover its phytochemical and antioxidant potential. After stress induction, the leaves were harvested at different day’s post-inoculation (dpi) and analyzed for phytoconstituents and antioxidant assays. Results: The data showed statistically significant differences among proteins, reducing sugars, total soluble sugars, proteases and amylase of the samples at different dpi under biotic and abiotic stress (P<0.05). Moreover, total flavonoid, phenolic constituents, DPPH, ascorbic acid, catalase, peroxidase and superoxide dismutase were significantly increased under stress (P<0.05). The phytochemical and antioxidant activities were altered that proved its effectiveness under induced conditions. Conclusion and Practical Implications: The results obtained indicated that the Allium sativum (garlic) grown under biotic and abiotic stress have certain phytoconstituents with improved antioxidant activity that may serve as a rich source for antioxidants and proteins that may be used as an alternate to synthetic formulations in food and pharmaceuticalsto improve health outcome. Keywords: Allium sativum, antioxidant, biotic, abiotic, phytoconstituents, stress